Diabetes Detection through Mathematical Modelling Approach - Twinkle Singh (Research and Applications Towards Mathematics and Computer Science Vol. 5, 2023)
The main objective of the current study is related to Diabetes disease. Diabetes is a disease of metabolism whose essential feature is excessive sugar in the blood and urine. In this disease the body is unable to burn off all it sugar, starches and carbohydrates which leads to serious pathological conditions. Second order differential equation has been constructed to describe the performance of BGRS during GTT and solution has been narrated over here. Interesting point is that the sociological factors play an important role in the Blood Glucose Regulatory System.